The Diamino Analogues of Privileged Corey–Bakshi–Shibata and Jørgensen–Hayashi Catalysts: A Comparison of Their Performance - Vargas-Caporali, Jorge; Juaristi, Eusebio (Synthesis, 2016)
α,α-Diarylprolinol derivatives are well-established families of organocatalysts that are widely used to promote diverse asymmetric reactions. The enantioinduction generated from these ligands is mainly due to the gem-diphenyl carbinol fragment. For this reason, the synthesis of diaza analogues seemed an evident and attractive issue to address in the development of alternative chiral ligands. Although the O→N substitution and subsequent derivatization at first glance looked simple, it was necessary to deal with various unexpected synthetic difficulties. It was established that suitable modifications of the side chain in the diaza analogues afford reaction yields and stereoselectivities that are comparable to those exhibited by the amino alcohol analogues. Nevertheless, various potential applications still remain undeveloped.1 Introduction2 Oxazaborolidines and Diazaborolidines in Borane-Mediated Reduction of Prochiral Ketones3 Organocatalyzed Asymmetric Epoxidations4 Assessing the Organocatalytic Capability of the α,α-Diphenylprolinol Diaza-Analogues through Benchmark Mannich and Michael Reactions
Keywords: CBS catalysts; diazaborolidines; chiral pyrrolidine derivatives; asymmetric organocatalysis; Thorpe–Ingold effect